A pilot study: relationship between Bisphenol A, Bisphenol-glucuronide and total 25 hydroxy vitamin D in maternal-child pairs in a South African population - Gounden, Verena; Naidoo, Rajen N.; Chuturgoon, Anil (Frontiers in Endocrinology, 2024)
Exposure to Bisphenol A (BPA) during early development particularly in-utero has been linked to a wide range of pathology. Over the last two decades the importance of vitamin D in maternal and child health has been highlighted. The aim of this pilot study was to examine the relationship of BPA and its naturally occurring metabolite BPA-glucuronide (BPA-g) with 25-hydoxy vitamin D (25OHD) levels in South African mother-child pairs. Third-trimester serum maternal samples and matching cord blood samples were analyzed for BPA and BPA-g using liquid chromatography tandem mass spectrometry (LC-MS/MS) and 25OHD3 and 25OHD2 using high performance liquid chromatography.A total of 58 maternal and child pairs were analyzed. More than fifty percent of maternalchild pairs were noted to be vitamin D deficient or insufficient using the Endocrine Society Practice guidelines cut-off of 50 nmol/L. Spearman rank correlation and Kruskal Wallis analysis did not show statistically significant relationship between cord 25OHD (total) and maternal and cord BPA-g concentrations. Analysis of covariance after controlling for confounders showed a significant relationship between cord BPA-g levels and cord 25OHD levels (p=0.03) as well as between maternal BPA-g levels (p=0.04) and cord total 25OHD levels (p=0.04). The findings of the current study indicate a possible relationship with BPA/BPA-g and foetal/early infant Vitamin D levels that needs to be further investigated in this population.